Diseño e implementación de módulo didáctico de un sistema automático de obtención de colores de pintura, obtenidos a partir de la mezcla de colores primaríos y su respectivo envasado - Garaycoa, Pablo (2010)
Before we have finished our studies in ESPOL, we realized that it would be useful to give a didactic module for the students of our carrier, that´s why we decided to build a mixing and canning module because it shows the two more common industry processes , such as making a recipe and the canning of a product. By means of a electric- pneumatic design we can control a paint mixing process for getting paint based on primary colours, in order to achieve the desired control of this process we have to apply our acquired knowledge during the carrier such us the correct use of sensors, actuators and Programmable Logic Controllers.